A positive deviance approach to understand gender relations and practices that support transformative adaptation: Insights from Kenya dairy households - Bullock, Renee; DuttaGupta, Tanaya; Miriti, Philip (Elsevier, 2025)
The impacts of climate change on livelihoods and livestock systems in East Africa are significant. Efforts to bolster resilience will require a concerted focus on social equity to foster transformative adaptation. We integrate a feminist lens in a positive deviance approach to better understand gender relations in dairy producing communities in Kenya. We make theoretical and methodological contributions and suggest practical application to support locally led scaling approaches. Data was collected through 20 sex disaggregated focus group discussions (FGDs) and 10 key informant interviews (KII) with a total of 199 research participants. We focus on women's and men's participation in decision-making to assess gendered agency and labor in households, dairy specific activities, and the uptake of climate innovations. Evaluating these relations provides a better understanding of equity in dairy producing households who are at the forefront of climate adaptation. Women's and men's practices vary, and, through a positive deviance inquiry, we find the common patterns in those practices to characterize the referent group using thematic analyses. Our empirical findings demonstrate that referent group norms, relations and practices are, by and large, inequitable in agency and labor in dairy households underpinned by social norms. Positive deviant practices occur at differential rates in diverse geographies. We extended the concept of positive deviance to a relevant and urgent development agenda, transformative adaptation, that, to support resilience, must address root causes of vulnerability. We advocate for increased efforts to utilize positive deviance in future climate adaptation studies to inform practical and locally led strategies.